2019
DOI: 10.1186/s12888-019-2119-2
|View full text |Cite
|
Sign up to set email alerts
|

Delayed effect of bifrontal transcranial direct current stimulation in patients with treatment-resistant depression: a pilot study

Abstract: Background Transcranial direct current stimulation (tDCS) is a non-invasive brain stimulation technique, which has yielded promising results in treating major depressive disorder. However, its effect on treatment-resistant depression remains to be determined. Meanwhile, as an emerging treatment option, patients’ acceptability of tDCS is worthy of attention. Methods This pilot study enrolled 18 patients (wome n = 13) with treatment-resistant un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 42 publications
3
14
1
Order By: Relevance
“…The idea of modulating social cognition by tDCS targeting the prefrontal cortex stems from studies showing the involvement of this region in social cognition (73), and its relationship with social cognitive deficits in MS (10). Unlike our study, 12 sessions of bifrontal tDCS improved social cognition in depressed patients (74). Moreover, a single session of anodal tDCS ameliorated social cognitive measures in healthy individuals [left prefrontal anodal stimulation, right frontopolar cathode; (75)], as in patients with neurodegenerative diseases [medial prefrontal anodal stimulation; in frontotemporal dementia (76) and in Parkinson's disease (77)].…”
Section: Tdcs and Social Cognitioncontrasting
confidence: 52%
“…The idea of modulating social cognition by tDCS targeting the prefrontal cortex stems from studies showing the involvement of this region in social cognition (73), and its relationship with social cognitive deficits in MS (10). Unlike our study, 12 sessions of bifrontal tDCS improved social cognition in depressed patients (74). Moreover, a single session of anodal tDCS ameliorated social cognitive measures in healthy individuals [left prefrontal anodal stimulation, right frontopolar cathode; (75)], as in patients with neurodegenerative diseases [medial prefrontal anodal stimulation; in frontotemporal dementia (76) and in Parkinson's disease (77)].…”
Section: Tdcs and Social Cognitioncontrasting
confidence: 52%
“…As our main aim was to identify potential fMRI‐based markers for training outcome, we did not assess possible cognitive and clinical transfer effects, which will be relevant for evaluating clinical relevance, and further studies are needed to establish the premises for optimizing the clinical potential for working memory interventions in individual stroke patients. It has furthermore been reported that potential beneficial effects of tDCS may emerge at a delayed stage after intervention (Goodwill, Teo, Morgan, Daly, & Kidgell, 2016; Li et al, 2019). As our last assessment was performed shortly after the final stimulation, any delayed effects may have been lost.…”
Section: Discussionmentioning
confidence: 99%
“…refs. 11 , 13 , 23 27 ), using stereotaxic mapping of brain coordinates in each individual. We hypothesized that Active-tDCS targeted at the left DLPFC would induce significant magnetic fields during stimulation in the same region, according to Ampere’s Law (hypothesis#1).…”
Section: Introductionmentioning
confidence: 99%